Structural behavior of non-pneumatic tires using finite element analysis - Azer, Mesutcan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2023., 2023)
Modern tire technology has revolutionized vehicle performance in terms of safety and comfort by combining improvements in production techniques, materials, and design. However, conventional tires have major drawbacks like punctures, pressure loss, and temperature fluctuations, leading to a reduction in efficiency and an increase in maintenance requirements. In order to overcome these limitations, the development of non-pneumatic tire (NPT) technology has gained importance. NPTs have been characterized by their airless design using durable materials such as solid rubber or foam with major advantages like puncture resistance, minimal maintenance, and excellent load-bearing capability. This study focuses on the structural behavior of the Michelin Unique Puncture-Proof Tire System (UPTIS) based NPT using the finite element analysis. For static vertical loading, the effects of collapsible spoke thickness, spoke angle, and reinforcement thickness on the vertical displacement, vertical stiffness, contact pressure, and rolling resistance are evaluated. Additionally, the steady-state rolling analysis of NPT is performed in order to investigate the dynamic characteristics which are contact pressure and shear stress distribution on the contact area in braking, freerolling, and traction states. As UPTIS and NPTs have been gaining more popularity in the automotive industry, the findings of this study contribute to understanding of the relationship between design parameters and NPT performance.
Keywords: Automobiles -- Tires.; Finite element method.